Baker's student encyclopedia of music. Volume one, A-G - Kuhn, Laura Diane (New York : Schirmer Books, 1999)
Contains entries that provide information about music, covering musicians, composers, compositions, instruments, musical terms, facts, and anecdotes; and includes illustrations and a comprehensive index. Arranged alphabetically from A-to-G.
Includes index.
Young Adult
Keywords: Music -- Dictionaries; Music -- Dictionaries